New Innovation in Utilizing Natural Dyes Ecoprint Pounding In the Dahlia Farmers Group, TTU-NTT Regency: Inovasi Baru Pemanfaatan Pewarna Alami “Ecoprint Pounding” Di Kelompok Tani Dahlia Kabupaten TTU-NTT - Noviana Mery Obenu; Maria Magdalena Kolo; Eduardus Edi; Yolanda Getrudis Naisumu (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The process of making a piece of woven fabric using natural dyes takes a long time, starting from collecting the materials to dyeing the yarn. This causes the weaving activists in the Dahlia Farmers Group to only be able to weave one piece of cloth in ± 3-4 days or even 1 week. The Dahlia Farmers Group has used natural dyes for generations, but the use of natural dyes is only on woven yarn and has not known and tried to make ecoprint. This prompted the Service Team to provide skills in the form of socialization and ecoprint training as a new innovation in the use of natural dyes. In addition, this training is also to instill knowledge and stimulate ideas about environmentally sustainable entrepreneurial products, thereby increasing income, and introducing additional products outside of traditional weaving. The approach adopted in this training, in addition to socialization explaining the principles of ecoprint, also focuses specifically on pounding techniques. Based on the results of the activity, it appears that the partners are enthusiastic and have a great interest in the training and the products produced, in the form of plant-patterned fabrics and bags with a variety of colors.